Understanding the role of parasites in food webs using the group model. (18th December 2017) - Michalska‐Smith, Matthew J.; Sander, Elizabeth L.; Pascual, Mercedes; Allesina, Stefano
Abstract: Parasites are ubiquitous and have been shown to influence macroscopic measures of ecological network structure, such as connectance and robustness, as well as local structure, such as subgraph frequencies. Nevertheless, they are often under‐represented in ecological studies due to their small size and often complex life cycles. We consider whether or not parasites play structurally unique roles in ecological networks; that is, can we distinguish parasites from other species using network structure alone? We partition the species in a community statistically using the group model, and we test whether or not parasites tend to cluster in their own groups, using a measure of "imbalance." We find that parasites form highly imbalanced groups, and that concomitant predation, in which a predator consumes a prey and its parasites, but not the number of interactions, improves the group model's ability to distinguish parasites from non‐parasites. This work demonstrates that parasites and non‐parasites interact in networks in statistically distinct ways, and that these differences are partly, but not entirely, due to the existence of concomitant predation. Abstract : Arranging species into groups based on the similarity of their interactions yields a surprising overlap with classifications of trophic strategy. Remarkably, this level of similarity is not attainable by using any of the commonly appreciated local structural differences between parasites and species employing other trophic strategies, but instead requires incorporation of the global network structure.